PENERAPAN CUSTOMER RELATION MANAGEMENT DALAM MENINGKATKAN JUMLAH PENGUNJUNG PADA HOTEL GRAND CENTRAL PEKANBARU - Debby Diana Sari; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The hotel is an industry engaged in lodging services. The emergence of new hotels makes old hotels increasingly active to improve service quality. The creation of customer satisfaction by the Grand Central Pekanbaru Hotel provides the benefits and reputation of the hotel to be good in the eyes of customers and also the profits obtained by the hotel will increase. The purpose of this study was to find out how the customer relations strategy, dissemination of information and also the media used by Grand Central Pekanbaru Hotels in increasing the number of visitors at the Grand Central Hotel Pekanbaru               This study uses qualitative research methods and data collection techniques are participant observation, interviews and documentation. The research subjects consisted of General Manager, Public Relations Hotel and F & B Hotel Manager. Then visitors to the Grand Central Hotel Pekanbaru. After the data is collected, the writer uses an interactive data analysis model presented by Miles and Huberman. The final stage of this analysis is to hold a validity check of the data.               The results showed that the Grand Central Pekanbaru Hotel custumer relations communication strategy included continuity of marketing, one to one marketing and partnering programs. The program is considered capable of maintaining and increasing the number of visitors to the Grand Central Pekanbaru Hotel. Media and promotions carried out by Hotel Grand Central Pekanbaru are well-promoted and effective.